Ювенильное море: [Сборник] / А. П. Платонов - Платонов Андрей Платонович (Центр. -Чернозем. кн. издательство, 1988)
Экземпляры: (20200128) / Инвентарный номер: 21446 / Цена: 4.00 / Сис.шифр: Р2 / Авт.знак: П37 / ББК: Р2